Galectin-9: A Suppressor of Atherosclerosis? - Yu, Jian; Zhu, Ruirui; Yu, Kunwu; Wang, Yue; Ding, Yan; Zhong, Yucheng; Zeng, Qiutang (Frontiers in Immunology, 2020)
It is no longer controversial that atherosclerosis is a vascular wall chronic inflammatory disease mediated by cells of innate and adaptive immunity. Galectin-9(Gal-9) seems to be a crucial regulator of T-cell immunity by inducing apoptosis in specific T-cell subpopulations associated with autoimmunity and inflammatory disease. Accumulating evidence showed that galectin-9 signaling via T-cell immunoglobulin mucin 3 (TIM-3) is concerned with different regulatory functions in autoimmunity, including direct depletion of pro-inflammatory T-cells, expanding the number of regulatory T cells, altering macrophages to an anti-inflammatory state and the induction of repressive myeloid-derived suppressor cells. In addition, anti-Tim-3-Ab administration increased atherosclerotic plaque formation by blocking Tim-3‒galectin-9 interaction. Hence, we hypothesize that galectin-9 may be a novel therapy for atherosclerotic disease. Further researches are needed to investigate the precise effect of galectin-9 in the process of atherosclerosis.